2022
DOI: 10.1101/2022.06.11.493219
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adaptation shapes local cortical reactivity: from bifurcation diagram and simulations to human physiological and pathological responses

Abstract: Human studies employing intracerebral and transcranial perturbations suggest that the input-output properties of cortical circuits are dramatically affected during sleep in healthy subjects as well as in awake patients with multifocal and focal brain injury. In all these conditions, cortical circuits react to direct stimulation with an initial activation followed by suppression of activity (Off-period) that disrupts the build-up of sustained causal interactions typically observed in healthy wakefulness. The tr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The phenomenon of cortical bistability entails a profound membrane hyperpolarization after a transient activity increase [10]. More precisely, after an initial activation, e.g., triggered by the external TMS-perturbation, neurons rapidly plunge into a silent down-state that disrupts the emergence of complex long-range responses and sustained interactions usually observed during wakefulness [9,10,41]. It has been suggested that this phenomenon is influenced by enhanced adaptation mechanisms such as activity-dependent potassium currents, decreased modulation from activating systems, and increased GABAergic inhibition [11][12][13]42].…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of cortical bistability entails a profound membrane hyperpolarization after a transient activity increase [10]. More precisely, after an initial activation, e.g., triggered by the external TMS-perturbation, neurons rapidly plunge into a silent down-state that disrupts the emergence of complex long-range responses and sustained interactions usually observed during wakefulness [9,10,41]. It has been suggested that this phenomenon is influenced by enhanced adaptation mechanisms such as activity-dependent potassium currents, decreased modulation from activating systems, and increased GABAergic inhibition [11][12][13]42].…”
Section: Discussionmentioning
confidence: 99%
“…Both dendritic decoupling and the breakdown of recurrent interactions are expected to result in dramatic decreases in the brain's capacity for integrated information. Along these lines, the collapse of complexity observed experimentally during sleep and in vegetative state patients is associated with a breakdown of feedback interactions [143][144][145][146] .…”
Section: Overarching Concepts: Richness and Complexitymentioning
confidence: 97%